IL-10 predicts the prognosis of patients with hepatitis B virus-related acute-on-chronic liver failure combined with spontaneous bacterial peritonitis - Liu, Linxiang; Xiao, Nanxi; Chen, Peng; Zhu, Xuan (Frontiers in Medicine, 2023)
Background Spontaneous bacterial peritonitis (SBP) is common in patients with hepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF). The prognostic value of interleukin-related serum markers for patients with ACLF is coming to the fore. However, there is an unmet need to predict the survival of such patients. We aimed to analyze the independent predictors of 28- and 90-day mortality in HBV-ACLF patients with SBP. Methods This was a retrospective study that included 368 patients with HBV-ACLF. In the SBP group, logistic regression analysis was used to understand the independent predictors of mortality at 28-day and 90-day. The accuracy of prediction was analyzed using the area under the receiver operating characteristic curve (AUROC). Finally, decision curve analysis (DCA) was used to determine the clinical utility value. Results Interleukin 10 (IL-10) levels were statistically significantly different between the HBV-ACLF group with SBP and without. Aspartate aminotransferase (AST), serum sodium, IL-10 and vasoactive drug treatment were independent risk factors for 28-day mortality. International normalized ratio (INR), AST and IL-10 were independent risk factors for 90-day mortality. IL-10 combined with the Chinese Severe Hepatitis B Study Group-ACLF II score (COSH-ACLF IIs) had excellent performance in predicting 28- and 90-day mortality (AUCs: 0.848 and 0.823, respectively). DCA analysis suggests promising clinical utility. Conclusion IL-10 is an independent predictor of mortality at 28- and 90-day in HBV-ACLF patients with SBP and predictive performance is improved when combined with COSH-ACLF IIs.